Business Suistainability Analysis pada BUM Desa - Muhammad Farkhan Dicki Samudera; Arimurti Krisbowo (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The purpose of this study wasto analyze the sustainability of the BUM Desa Bumi Indomakmur Kalanganyar. The research method used is qualitative with a descriptive approach using The Fifth CapitalModel theory. Data collection was done through interviews with key informants, observation, and documentation. The results obtained in this study are: 1) Natural capital has not been fulfilled because BUM Desa obtains raw materials by purchasing, 2) Human Capital has been fulfilled with training and a clear remuneration system, 3) Social Capital has not been fulfilled because BUM Desa does not have an SOP, 4) Manufacturing Capital has not been fulfilled because BUM Desa does not use other machines/technology due it not focuses on production but only on services, and 5) Financial Capital has also not been fulfilled because the financial condition of the business in reality does not match the capital owned and BUM Desa still has an unfavorable image in the community due to the similarity of business forms.